IMPACTOS DO ESPORTE NA SAÚDE MENTAL DE ATLETAS ADOLESCENTES (Editora Impacto Científico, 2025)
The present study aimed to examine the impact of sports on athletes’ mental health, highlighting both physical and psychological benefits, as well as exploring how these factors influence the well-being and sociability of young practitioners. The research sought to identify ways to minimize negative impacts, improve athletic performance, and promote a healthier environment. The central issue was related to the increase in anxiety, stress, and burnout during competition preparation periods, especially among young athletes. These factors, combined with family and interpersonal pressures, harm not only performance but also the athletes’ mental health, affecting both their sporting and personal lives. The article explored how high physical and emotional demands psychologically affect young athletes, showing how these challenges impact their self-confidence and performance. In addition, the effects of external factors, such as injuries and social pressures, were discussed, as well as the importance of strengthening cohesion and communication among team members. The methodology included naturalistic observation, questionnaire application, and the presentation of relaxation techniques and discussion circles with young handball athletes from the municipality of Foz do Iguaçu, PR. These methods revealed that excessive training loads, combined with external factors, triggered symptoms of burnout, affecting both performance and psychological well-being. It was concluded that interventions focused on emotional support, such as Cognitive Behavioral Therapy (CBT), could significantly improve athletic performance and reduce negative psychological impacts. Strengthening this support and creating a more balanced sports environment were considered essential for the healthy development of young athletes.DOI: https://doi.org/10.56238/edimpacto2025.090-009